For documentary : twelve essays - Vaughan, Dai (University of California Press, 1999)
These essays offer fresh and challenging insights into documentary. Vaughan makes his starting point plain: 'Most of us would feel that the word 'documentary' had not justified its place in the dictionary if the films so called did not manifest some relationship with the world not shared by others.' That elusive relationship is the subject of his eloquent reflections and analyses.
Includes index.
Keywords: Documentary films -- History and criticism.; Documentaires -- Histoire et critique.; LANGUAGE ARTS & DISCIPLINES -- Journalism.; Documentary films; Dokumentarfilm; Documentaires.; Films documentaires -- Histoire et critique.; Criticism, interpretation, etc.